2021
DOI: 10.1371/journal.pone.0253135
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of point-of-care testing and treatment for sexually transmitted and genital infections in pregnancy in low- and middle-income countries: A systematic review

Abstract: Background Sexually transmitted and genital infections in pregnancy are associated with adverse pregnancy and birth outcomes. Point-of-care tests for these infections facilitate testing and treatment in a single antenatal clinic visit and may reduce the risk of adverse outcomes. Successful implementation and scale-up depends on understanding comparative effectiveness of such programmes and their comparative costs and cost effectiveness. This systematic review synthesises and appraises evidence from economic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…In LMICs, a major barrier to scale-up of etiologic STI testing is cost. 22 In resource-constrained settings where reporting of multiple partners is low and partner treatment is well documented, it may be feasible to reduce STI testing costs by removing the recommendation for a routine test of cure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In LMICs, a major barrier to scale-up of etiologic STI testing is cost. 22 In resource-constrained settings where reporting of multiple partners is low and partner treatment is well documented, it may be feasible to reduce STI testing costs by removing the recommendation for a routine test of cure.…”
Section: Discussionmentioning
confidence: 99%
“…As countries consider expanding the availability of STI testing during antenatal care, decisions must be made about when to offer screening and whether and when to offer tests of cure and rescreening. In LMICs, a major barrier to scale-up of etiologic STI testing is cost 22 . In resource-constrained settings where reporting of multiple partners is low and partner treatment is well documented, it may be feasible to reduce STI testing costs by removing the recommendation for a routine test of cure.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid point-ofcare (POC) screening for the presence of BV-related biomolecules may provide an early indication of women at risk for BV-related pregnancy diseases regardless of symptomology. 10 Recent studies suggest the displacement of healthpromoting vaginal bacteria (i.e., Lactobacillus spp.) and outgrowth of potential pathogenic bacteria are associated with increased levels of biochemicals known as biogenic amines (e.g., putrescine, cadaverine, and tyramine) and elevated vaginal pH.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other methods sufficient to identify asymptomatic BV, such as microscopy (i.e., Nugent criteria) or molecular diagnostics, vary in their availability for women due to differences in healthcare access. Rapid point-of-care (POC) screening for the presence of BV-related biomolecules may provide an early indication of women at risk for BV-related pregnancy diseases regardless of symptomology . Recent studies suggest the displacement of health-promoting vaginal bacteria (i.e., Lactobacillus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the evidence base for the cost and costeffectiveness of PoC testing for STIs in pregnancy has grown, including in LMICs. A recent systematic review 34 identified that the bulk of these studies was conducted in Africa or Latin and South America, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] with no studies undertaken in East Asia or the Pacific. Most of the studies investigated the cost and cost-effectiveness of PoC testing for syphilis in pregnancy compared with no screening, syndromic management or onsite laboratory testing.…”
Section: Introductionmentioning
confidence: 99%